Impact of financial crisis on the Islamic banks’ customers: a case of Malaysia - Abdul Razak, Dzuljastri; Mohammed , Mustafa Omar; Md Zabri, Mohd Zaidi; Abdullah, Kalthom (2014)
The recent 2008 global financial crisis was dubbed as the worst crisis since the Great Depression. Several conventional banks were affected. However, the effect of the crisis on Islamic banks was marginal. There is quite a volume of literature that has discussed this financial crisis and how Islamic banks are somewhat insulated against the corollaries of such catastrophe. Some of these studies have argued that Islamic banking emerged relatively unscathed and remains resilient due to its salient features, which includes; inter alia, emphasis on ownership prior to transacting and, avoidance of riba’(usury) and gharar (speculative)-based transactions. The present study examines the extent to which Islamic bank customers are aware of the salient features of Islamic banking and finance, and the effect of the crisis on their lifestyle. A convenient sampling of postgraduate students of International Islamic University Malaysia (IIUM) has been used due to their knowledge of the subject under investigation. The results from the descriptive analysis show that generally the respondents are aware of the salient features of Islamic banking and finance that mitigate the impact of financial crisis. Further, the respondents are also aware of adverse impacts of the crisis. The study has provided suggestions for future research in the concluding remarks.